2011
DOI: 10.3390/molecules16075422
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Key Fragments of Amphidinolide Q — A Cytotoxic 12-membered Macrolide

Abstract: β-Hydroxy aldehyde and alkyl ketone moieties were effectively synthesized as key intermediates of amphidinolide Q, a cytotoxic macrolide from the cultured dinoflagellate Amphidinium sp.. The asymmetric center of the former derivative was produced by Sharpless asymmetric epoxidation, followed by E-selective 1,4-addition to give the sp2 methyl group. Derivatization of the L-ascorbic acid derivative by Evans asymmetric alkylation and Peterson olefination provided the latter intermediate. The coupling reaction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Following literature methodology, 31 to a solution of compound 10 (0.36 g, 1.0 mmol) dissolved in anhydrous THF (15 mL) under N 2 at 0 °C was added Et 3 N (0.79 mL, 5.7 mmol). The reaction was cooled to 0 °C, and pivaloyl chloride (0.19 mL, 1.5 mmol) was added dropwise.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following literature methodology, 31 to a solution of compound 10 (0.36 g, 1.0 mmol) dissolved in anhydrous THF (15 mL) under N 2 at 0 °C was added Et 3 N (0.79 mL, 5.7 mmol). The reaction was cooled to 0 °C, and pivaloyl chloride (0.19 mL, 1.5 mmol) was added dropwise.…”
Section: Methodsmentioning
confidence: 99%
“…The crude compound was purified through a short column of silica gel (MeOH/DCM, 1% isocratic elution) to give compound 10 as colorless crystals in 85% yield (1.78 (11). Following literature methodology, 30 to a solution of compound 10 (0.36 g, 1.0 mmol) dissolved in anhydrous THF (15 mL) under N 2 at 0 °C was added Et 3 N (0.79 mL, 5.7 mmol). The reaction was cooled to 0 °C, and pivaloyl chloride (0.19 mL, 1.5 mmol) was added dropwise.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Cytotoxic macrolides produced by members of the primarily benthic dinoflagellate genus Amphidinium, and hence called amphidinolides (Figures 4A-E), have shown hemolytic activity (Yasumoto et al, 1987), as well as evidence of cytotoxicity against cancer cell lines, and antifungal properties (Kobayashi et al, 1991;Bauer et al, 1995a,b;Kobayashi et al, 2002;Tsuda et al, 2007;Espiritu et al, 2017). Within the last decade, interest in the toxigenicity of this genus has increased because some species, namely the type species A. carterae Hulburt 1957 and members of the A. operculatum Claparède & Lachmann, 1859 species complex, are known to produce ichthyotoxic substances (Kobayashi et al, 1991;Satake et al, 1991;Tsuda et al, 1994;Bauer et al, 1995a,b). In most cases, bioactivity (and in higher doses toxicity) is assumed to be related to various polyketides and macrolides isolated from different species of the genus (Kobayashi et al, 1991;Bauer et al, 1995a,b;Kobayashi et al, 2002;Tsuda et al, 2007;Espiritu et al, 2017).…”
Section: Determination Of Toxin Composition Occurrence and Associatementioning
confidence: 99%
“…[102,103] Even though it has moderate complexity only one total synthesis is reported so far. [104] Some synthetic studies have also been demonstrated. [105] Total synthesis of amphidinolide Q was commenced from meso-diol 56, that after several steps afforded aldehyde 57.…”
Section: -Membered Macrolidesmentioning
confidence: 99%